Atropisomerism in N1‐aryl Substituted 3, 4‐dihydropyrimidin‐2(1H)‐thiones. Issue 42 (16th November 2020) - Gonçalves, Itamar L.; Davi, Leonardo; Machado das Neves, Gustavo; Porto Kagami, Luciano; Garcia, Solange C.; Oliveira Battastini, Ana M.; Figueiró, Fabrício; Faria Santos Canto, Rômulo; Merlo, Aloir A.; Eifler‐Lima, Vera L.
Abstract: Dihydropyrimidinone/thiones (DHPMs) are heterocycles widely explored due to their ability to interact with different pharmacological targets. We report herein the C–N axial chirality in a DHPM scaffold with the presence of various substituents at the ortho ‐position of the aromatic ring linked to the N1. This structural feature produced atropisomerism due to the restricted rotation around the C−N bond. The atropisomerism in DHPMs was investigated by NMR, HPLC, and in silico experiments. The effect of the solvent, microwave radiation, temperature, and substituent at the ortho position on the selectivity of the reaction was examined. Abstract : The results reported here are the first investigation of atropisomerism in Biginelli compounds. Was identified a C−N axial chirality in 3, 4‐dihydropyrimidin‐2(1H)‐thiones with substituents at the ortho ‐position of the aromatic ring linked to the N1. The solvent, microwave radiation, temperature, and substituent at the ortho ‐position affected the atropisomers ratio. Also, the atropisomerism in 3, 4‐dihydropyrimidin‐2(1H)‐thiones was investigated by NMR, HPLC, and in silico experiments.